Radiocobalt-Labeling of a Polypyridylamine Chelate Conjugated to GE11 for EGFR-Targeted Theranostics - Lorraine Gaenaelle Gé; Mathias Bogetoft Danielsen; Aaraby Yoheswaran Nielsen; Mathias Lander Skavenborg; Niels Langkjær; Helge Thisgaard; Christine J. McKenzie (Molecules)
The overexpression of the epidermal growth factor receptor (EGFR) in certain types of prostate cancers and glioblastoma makes it a promising target for targeted radioligand therapy. In this context, pairing an EGFR-targeting peptide with the emerging theranostic pair comprising the Auger electron emitter cobalt-58m (58mCo) and the Positron Emission Tomography-isotope cobalt-55 (55Co) would be of great interest for creating novel radiopharmaceuticals for prostate cancer and glioblastoma theranostics. In this study, GE11 (YHWYGYTPQNVI) was investigated for its EGFR-targeting potential when conjugated using click chemistry to N1-((triazol-4-yl)methyl)-N1,N2,N2-tris(pyridin-2-ylmethyl)ethane-1,2-diamine (TZTPEN). This chelator is suitable for binding Co2+ and Co3+. With cobalt-57 (57Co) serving as a surrogate radionuclide for 55/58mCo, the novel GE11-TZTPEN construct was successfully radiolabeled with a high radiochemical yield (99%) and purity (>99%). [57Co]Co-TZTPEN-GE11 showed high stability in PBS (pH 5) and specific uptake in EGFR-positive cell lines. Disappointingly, no tumor uptake was observed in EGFR-positive tumor-bearing mice, with most activity being accumulated predominantly in the liver, gall bladder, kidneys, and spleen. Some bone uptake was also observed, suggesting in vivo dissociation of 57Co from the complex. In conclusion, [57Co]Co-TZTPEN-GE11 shows poor pharmacokinetics in a mouse model and is, therefore, not deemed suitable as a targeting radiopharmaceutical for EGFR.